Knowledge and practice gaps and research priorities for clay-related phenomena in the minerals processing value chain - Gräfe, M.; McFarlane, A.; Klauber, Craig (2017)
© Commonwealth Scientific and Industrial Research Organisation (CSIRO) 2017. Introduction This final chapter addresses priority research needs for either creating new knowledge of how clays affect one or more unit processes in the mineral processing value chain (MPVC) or to improve utilization of existing knowledge/techniques to assess the impacts or characteristics of clays through improved best practice. These are referred to in this chapter as knowledge and practice gaps, respectively. Knowledge gaps in general were synthesized by the respective chapter authors and the editors subsequently refined the distinction between knowledge and practice gaps. The knowledge and practice gaps are succinctly summarized in Table 10.1. All author teams have provided a conceptual view as to how the knowledge/practice gap could be addressed as well as what the perceived research outcomes would be. In total, the authors identified 15 knowledge/practice gaps and research needs based on the public domain literature surveyed. Review Statistics This review has compiled and processed information from more than 1100 references available in the public domain, not counting data compiled for the preg-robbing (74) and characterization (~ 400) tables in Chapter 1. The range of citations used per chapter was between 52 and 212 for a page range of 20 to 72; on average each chapter used 128 ± 49 citations or 3 ± 1 citations per page. Practice Gaps A principal outcome of this book has been a collation of established knowledge regarding clays and their impact upon mineral processing. Since clays affect a range of unit processes across commodities, site-specific studies can remain cloistered and not readily useful to new situations. While such site-specific information could provide useful hypotheses for clay behaviour at other mines (with different geology and processing operations), any casual application of such knowledge could be counterproductive. Likewise, insights offered by applied research into ‘pure’ clay systems need to be critically reviewed and tested within given operational contexts. In light of the existing significant volume of clay knowledge, the practical question is how to best utilize this to improve the effectiveness and efficiency of mining, beneficiation, processing and disposal operations.